DSM-5 cultural and personality assessment of extreme overvalued beliefs. (September 2021) - Rahman, Tahir; Zheng, Lingjin; Meloy, J. Reid
Abstract: Lone actor targeted violence is often the result of pathological fixations driven by extreme overvalued beliefs. An extreme overvalued belief is shared by others in a person's cultural, religious, or subcultural group. The belief is often relished, amplified, and defended by the possessor of the belief and should be differentiated from a delusion or obsession. Over time, the belief grows more dominant, more refined, and more resistant to challenge. The individual has an intense emotional commitment to the belief and may carry out violent behavior in its service. The belief becomes increasingly binary, simplistic, and absolute. We discuss the phenomenology, historical origins and application of extreme overvalued belief which was derived from the seminal work of the 19th century German neuropsychiatrist, Carl Wernicke. We discuss how delusions are different from extreme overvalued belief. Targeted violence motivated by political, religious, racial, sexual or other shared ideologies, and often fueled through online interaction are discussed and applied to well known cases, including Anders Breivik, the Unabomber, assassins such as John Wilkes Booth, Osama bin Laden, Incels, anti-LGBTQ, Sovereign Citizens, violent jihadists, and neoNazis. The DSM-5 models on cultural formulation and alternative personality disorder are presented here as important contributions to clearly understanding cases involving extreme overvalued beliefs. Highlights: Obsessions, delusions and extreme overvalued beliefs are important cognitive drivers of fixation pertinent in threat assessment. Lone actor terrorism, assassinations and online radicalization are often motivated by extreme overvalued beliefs. The DSM-5 has sections on personality and culture which are of critical importance when formulating cases involving extreme overvalued beliefs.